A bio-inspired fluorescent nano-injectable hydrogel as a synergistic drug delivery system. (28th January 2021) - Xu, Yue; Yang, Mingming; Ma, Qiyue; Di, Xiang; Wu, Guolin
Abstract : A nano-injectable hydrogel with fluorescence properties and controlled sequential release of dual drugs. Abstract : Synergistic drug therapy has proven to be an effective strategy for various disease states. An injectable nano-hydrogel has been successfully prepared by random copolymerization of N -isopropylacrylamide (NIPAM) and acrylic functionalized nucleobase (adenine) for synergistic drug delivery. Different from ordinary polymeric hydrogels, the prepared injectable hydrogel showed a special phase-separated structure, combining nano-particles and macro-hydrogels, and potentially became useful as a dual drug carrier with a sequential release of different drug species. In addition, the obtained nanogels demonstrated fluorescence characteristics in a broad concentration range, without emission quenching at high concentrations. This feature is particularly important for possible visualization and imaging purposes. The studied material may represent a suitable candidate for fluorescent biological probes and dual drug delivery systems with intelligent responsiveness.